Under the blood-red sun - Salisbury, Graham (New York, N.Y. : Bantam Doubleday Dell Books for Young Readers, 1995)
Tomikazu Nakaji's biggest concerns are baseball, homework, and a local bully, until life with his Japanese family in Hawaii changes drastically after the bombing of Pearl Harbor in December 1941.
Originally published: New York : Delacorte Press, c1994.
"A Yearling book."
4-6
640
640
Keywords: Pearl Harbor (Hawaii), Attack on, 1941 -- Fiction; World War, 1939-1945 -- Fiction; Japanese Americans -- Fiction; Hawaii -- Fiction